2012
DOI: 10.1038/modpathol.2012.77
|View full text |Cite
|
Sign up to set email alerts
|

Succinate dehydrogenase-deficient GISTs are characterized by IGF1R overexpression

Abstract: Succinate dehydrogenase-deficient gastrointestinal stromal tumors (GISTs) demonstrate unique pathological and clinical features, including the absence of activating mutations of KIT and PDGFRA, and primary resistance to imatinib. They arise exclusively in the stomach and account for 5-7.5% of all adult stomach GISTs and the great majority of these tumors in childhood. Insulin-like growth factor 1 receptor (IGF1R) overexpression has been associated with wild-type and pediatric GISTs. We propose that IGF1R overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 25 publications
3
32
2
Order By: Relevance
“…In a set of 16 patients with KIT/PDGFRA WT GIST, all eight SDH-deficient KIT/PDGFRA WT tumours were SDHB negative and showed IGF1R overexpression, three NF1-related tumours were SDHB positive and IGF1R negative, and, among five unselected KIT/PDGFRA WT upper GIST, two were SDHB negative and showed IGF1R overexpression and three were SDHB positive and IGF1R negative, suggesting that IGF1R overexpression could be a feature of SDH-deficient GIST as a group, rather than of paediatric or KIT/PDGFRA WT GIST per se 68. In a small series of patients, all four patients with KIT/PDGFRA WT GIST displaying an IGF1R overexpression showed inactivating nonsense or missense SDHA mutations in the coding sequences, compared with respect to either KIT/PDGFRA mutant or KIT/PDGFRA WT GIST without SDH mutations 69.…”
Section: Non-syndromic Kit/pdgfra Wt Gistmentioning
confidence: 93%
“…In a set of 16 patients with KIT/PDGFRA WT GIST, all eight SDH-deficient KIT/PDGFRA WT tumours were SDHB negative and showed IGF1R overexpression, three NF1-related tumours were SDHB positive and IGF1R negative, and, among five unselected KIT/PDGFRA WT upper GIST, two were SDHB negative and showed IGF1R overexpression and three were SDHB positive and IGF1R negative, suggesting that IGF1R overexpression could be a feature of SDH-deficient GIST as a group, rather than of paediatric or KIT/PDGFRA WT GIST per se 68. In a small series of patients, all four patients with KIT/PDGFRA WT GIST displaying an IGF1R overexpression showed inactivating nonsense or missense SDHA mutations in the coding sequences, compared with respect to either KIT/PDGFRA mutant or KIT/PDGFRA WT GIST without SDH mutations 69.…”
Section: Non-syndromic Kit/pdgfra Wt Gistmentioning
confidence: 93%
“…35 Recently, the correlation between the overexpression of the insulinlike growth factor receptor 1 (IGF1R) protein and the status of SDH complex deficiency in KIT/PDGFRA wild-type GIST has been described suggesting that the IGF1R overexpression in this subset of patients may be driven by the loss of function of the SDH complex. [36][37][38][39] Finally, we would like to emphasize that, currently, the majority of KIT/PDGFRA wild-type GIST do not harbor mutations in SDH complex or do not present SDH deficiency, so their molecular background is still unknown. The discovery of the oncogenetic event in this GIST population still represents a great challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 85e90% of tumors have KIT (cd117) or PDGFRA mutation. Molecular studies of adult GISTS have confirmed activating mutations in the KIT gene (exons 9,11,13,17) in 90%, most frequently in exon 11. These distinctive KIT mutations have clinical and treatment implications [9].…”
Section: Gistmentioning
confidence: 94%
“…Activation of insulin like growth factor1-receptor (IGF1R) signaling is noted in these tumors and may play a role in their pathogenesis (Fig. 3) [12,16,17]. The treatment of GISTs in this entity remains to be defined.…”
Section: Gistmentioning
confidence: 98%